MEANING OF THE COLLECTION IN VAGINAL VAULT IMMEDIATELY AFTER SURGERY HYSTERECTOMIES VAGINALES - Siu, Alejandro (2015)
OBJETIVE: To establish the relation between the ultrasound determined vaginal dome collection following vaginal hysterectomy and the forthcoming complications. SETTING: Gynecology Service, 5-II Pavillion, Gynecology and Obstetrics Department, Arzobispo Loayza Hospital, a teaching hospital, between August 2001 and March 2002. MATERIAL AND METHODS: Each of 153 patients with elective vaginal hysterectomy had pelvic ultrasound done at the third post-opera tive day. The processed information was analyzed and considered as statistically significant with p < 0,05. RESULTS: Average age was 56 year-o1d and parity 7, respectively. There were 40,5% complications, two thirds of infectious origin main1y due to urinary tract infections secondary to bladder catheter permanence for longer than 72 hours. The other third was related to vaginal dome infection and hematoma. In a few cases there were failures in the surgical procedures. CONCLUSION: The presence of vaginal dome collection by ultrasound in the immediate post-operative period following vaginal hysterectomy signified an increase of 77 times the risk of having a complication at such level.